Sustained improvement in cognitive and emotional status of apneic patients after prolonged treatment with positive airway pressure - Joseph, Sharon; Zuriqat, Muqdad; Husari, Ahmad (Southern medical journal (Birmingham, Ala.), 2009)
Obstructive sleep apnea-hypopnea syndrome (OSAH) is associated with impairment of cognitive functions and disturbances in emotional status. The aim of this study was to objectively evaluate the benefits of prolonged and sustained treatment for OSAH at two sleep centers serving rural community hospitals. Fifty-six patients diagnosed with OSAH syndrome underwent Cognistat, Beck Depression Inventory (BDI) and Millon Behavioral Medicine Diagnostic Inventory (MBMD) testing before initiation of treatment. Repeated testing after six months of therapy with positive airway pressure (PAP) was performed. Significant improvements were noted in the BDI scale scores and a reduction in the MBMD scores reflected initial abnormal clinical personal symptoms that improved with treatment. MBMD analysis showed subjects with fewer symptoms of anxiety post baseline, which were sustained at 6 months post-treatment. Memory function improved as reflected by performance on the Cognistat. Women were observed to have a higher post-treatment BDI and younger patients appeared to have more shifts for improvement than older subjects in depressive symptomatology. These results indicate that prolonged and sustained PAP therapy is effective in restoring some of the deficiencies in patients with OSAH, particularly in terms of memory, depression, anxiety and increased psychological pathology.